PENINGKATAN KUALITAS PENGAJAR AL-QUR’AN MELALUI SEMINAR PEMBINAAN TAHSIN ASATIDZ LPQ KECAMATAN MIJEN OLEH BADKO LPQ KOTA SEMARANG - Kurnia Muhajarah; Kun Hayyuningtyas (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The Al-Qur'an Educational Institution (LPQ) is a vital center for early childhood moral education that is common in society, and being a society that is aware of moral and religious moral education should give more space and attention to these educational institutions. Outside of formal school education, LPQ has an important role. Given the importance of learning at LPQ, it is very important to also pay attention to the qualifications of teachers at LPQ, there must be an intense increase in human resources in order to achieve the noble goal of forming TPQ. Departing from these problems, there must be real attention and guidance for teachers at LPQ, the quality of teachers (asatidz LPQ) greatly affects the quality of understanding of students (santri LPQ). City LPQ BADKO As the coordinating agency for LPQs throughout the city of Semarang, they held a seminar on tahsin coaching for LPQ asatidz throughout Mijen District with the hope of increasing the quality of LPQ asatidz. This study uses a literature review method, problem analysis, then research and results. Based on the results of this study, it is known that the tahsin coaching seminar is quite effective in improving the quality of al-Qur'an teachers, which in this discussion is asatidz LPQ throughout Mijen District, especially in the ability to tahsin al-Qur'an. With a few notes, suggestions for improvement for the next coaching so that coaching can really maximize the human resources of asatidz LPQ.